2021
DOI: 10.1088/1755-1315/782/4/042008
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and cover percents of macroalgae species in intertidal zone of Pane

Abstract: Macroalgae or often referred to as seaweed is very abundant in Indonesian waters especially sea waters, including in Central Tapanuli. But it is unfortunate because not many people know about it, even though the seaweed has many benefits. This study aims to determine the amount of macroalgae cover and their diversity on one island in Central Tapanuli, namely Pane Island. This research was conducted from July to September 2019 in intertidal zone of Pane island with three observations, once a month. At the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…is found in the waters of Pane Island in North Sumatera. Based on [6] it was found that the composition of the most species of macroalgae is Sargassum sp. equal to 21.39%.…”
Section: Introductionmentioning
confidence: 99%
“…is found in the waters of Pane Island in North Sumatera. Based on [6] it was found that the composition of the most species of macroalgae is Sargassum sp. equal to 21.39%.…”
Section: Introductionmentioning
confidence: 99%
“…can live in coral habitats with a depth of 0.5 -10 meters with a talus size that reaches 2 meters. [2] stated that macroalga Sargassum sp. type is also found in the waters of Pane, Tapanuli Tengah Regency which is located not far from Poncan Gadang Island.…”
Section: Introductionmentioning
confidence: 99%